PENGARUH JUMLAH KUNJUNGAN WISATAWAN TERHADAP RETRIBUSI OBYEK WISATA DI KABUPATEN SUMBAWA (Studi Pada Obyek Wisata Pantai Saliper Ate) - Furna Aprianti; Ahmad Rafiudin; S Suprianto (Jurnal Ekonomi & Bisnis, 2022)
This study aims to determine the effect of the number of tourist visits on the tourist attraction fees in Panta Saliper Ate in 2016-2020. The data source used is secondary data, and uses data collection methods in the form of documentation obtained from the Department of Youth, Sports and Tourism. The data analysis technique was carried out using simple linear regression analysis techniques, individual parameter hypothesis testing (t test), and coefficient of determination test (R2). The results of this study indicate that the variable number of tourist visits has a positive and significant relationship to tourist attraction fees on Saliper Ate Beach during the 2016-2020 period. This implies that the higher the number of tourist visits, the retribution for tourism objects in Sumbawa Regency will increase, and vice versa. The ability of the variable number of tourist visits to explain changes in user fees for the tourist attraction of Saliper Ate Beach, Sumbawa Regency is 81.3%, while the remaining 18.7% is influenced by other variables outside this research model.